IKTIOFAUNA DI HILIR SUNGAI KLAWING KABUPATEN PURBALINGGA, JAWA TENGAH - Taufik Budhi Pramono; Diana Arfiati; Maheno Sri Widodo; Uun Yanuhar (Faculty of Science and Technology University Ibrahimy, 2018)
The status and potential of ichtyofauna resources in freshwaters, especially downstream of the river, must be monitored and evaluated frequently. Land use along the downstream river is often used as mining and industrial activities. The purpose of this study was to find out ichtyofauna in down stream of the Klawing Purbalingga River in Central Java. The study was conducted in January-March 2017 with descriptive exploratory method. Sampling using gill nets with the help of local fishermen. The fish obtained were identified and grouped by family to the species level. The results showed that in the down stream of the Klawing River there were species diversity consisting of 13 species, 7 families and 13 genera. Ichtyofauna from Cyprinidae family dominate as many as 6 species followed by Bagridae family 2 species. One introduced species of Osphronemus gouramy and one invasive alien fish species Hypostomus plecostomus and other species were indigenous species.